How and when was the lighthouse of positive discipline lit? (Journal of Parents and Teachers, 2023)
The skills outlined in positive discipline are achieved because during class meetings children are creating a sense of belonging and significance. Children have the opportunity to give and receive recognition. They each have a voice in the circle and suggest ideas for solving the challenges they face. From practice they learn to contribute and develop life skills and this also helps to improve the classroom climate.
Keywords: positive discipline; assembly; firmness; kindness; behaviour